Transformational Leadership Styles and Human Resource Management Challenges In The Era of Society 5.0 - Naila Nisrina Soliha; Havis Aravik; Ahmad Tohir (Jurnal Bisnis dan Manajemen (JURBISMAN), 2026)
The development of the Society 5.0 era has brought changes in human resource (HRM) management, characterized by the use of human-centric digital technology. This situation has triggered various challenges in modern HRM management, including the need for new competencies, adaptation to technology, and changes in work patterns. Transformational leadership is seen as playing a crucial role in addressing these challenges because it can encourage change, increase motivation, and develop human resource potential. This article aims to examine the role of transformational leadership in addressing HRM management challenges in the Society 5.0 era. The method used is a literature review, reviewing various relevant scientific sources. The results of the study indicate that transformational leadership contributes to creating adaptive and humanistic HRM management in the Society 5.0 era.